The youth organization and implication for spare time in Ciudad Juárez - Reyes, Aida Yarira (Theomai Journal Critical Studies about Society and Development, 2019)
http://www.revista-theomai.unq.edu.ar/NUMERO_40/4.%20Reyes%2040.pdf